Analysis of Accounting Information System for Raw Material Inventory at PT. Smart Tbk. Padang Halaban - Rani Rufmana Pohan; Laylan Syafina; Yenni Samri Juliati Nasution (PT Mattawang Mediatama Solution, 2024)
The Accounting Information System (AIS) is a vital component in providing financial and accounting data, along with information related to daily accounting transactions. This research focuses on evaluating the effectiveness of AIS using ERP-SAP in managing raw material inventory and supporting production efficiency at PT. Smart Tbk. Padang Halaban, a palm oil plantation company. The qualitative descriptive method was employed to gather data through literature review, interviews, and direct observations. The results of the study indicate that the implementation of AIS using ERP-SAP has improved the standard of financial reporting, meeting the required qualitative criteria. However, limitations exist in the AIS application, particularly regarding suboptimal raw material inventory tracking and integration issues between different systems, such as inventory and accounting systems, leading to data discrepancies. The conclusion drawn from this research highlights the necessity for adjustments, developments, and improvements in AIS features to meet the specific company requirements. The implications of these findings emphasize the importance of continuously optimizing AIS to support more efficient and accurate business processes, while adapting to technological advancements and company needs.